On the taxonomic status of Chactas camposi Mello-Leitão, 1939 (Scorpiones, Chactidae) - Ochoa, José A.; Pinto-Da-Rocha, Ricardo (Zootaxa, 2012)
The true taxonomic status of the chactid scorpion Chactas camposi Mello-Leitão, 1939 from Ecuador is established basedin the recently discovered holotype female, until now considered lost, at the Museu Nacional do Rio de Janeiro. In baseon the analysis of the external morphology, we transfer this species to the genus Teuthraustes Simon, 1878. A detailedredescription and diagnosis according to modern standards are provided. Teuthraustes camposi comb. n. is closely related with Teuthraustes whymperi (Pocock, 1893) from Ecuadorian provinces Pichincha and Cotopaxi.